Geomorphology and Physical Oceanography of the Lakshadweep Coral Islands in the Indian Ocean - Prakash, T.N; Nair, L. Sheela; Shahul Hameed, T.S (SpringerBriefs in Earth Sciences,, 2015)
The Lakshadweep islands are a group of 36 coral islands in the Indian Ocean. These small islands are unique for their aquatic bio-diversity and vast blue lagoons. This book presents the results of studies done by the authors during the period 1990 to 2009 that address the beach morphology, hydrodynamics, energy resources and management options with special reference to the issue of both natural and anthropogenic coastal erosion. The relatively low island elevation makes the islands more susceptible to high-wave attack and coastal flooding during adverse weather conditions. The islands are also prone to risks from episodic events like cyclones and deep depressions. This highlights the need for a comprehensive study of the wave, climate and coastal processes at work during different seasons to delineate the factors responsible for shoreline changes and also to identify the locations that need protection and the management options. This book will serve as a guide to researchers, scholars and students who are interested in the coastal processes of coral islands.